Lay health worker intervention in pre-diabetes management: Study protocol of a pragmatic randomized controlled trial for Chinese families living in inadequate houses - Chan, Crystal Ying; Hoi, Becky Pek-kei; Wong, Eliza Lai-yi (Frontiers in Public Health, 2022)
Introduction: Lay health workers, despite their lack of formal trainings, are important partners in providing accessible care to people with risk to develop diabetes in the community. While pre-diabetes and diabetes are more prevalent among people with low socio-economic status, including those living in inadequate houses. However, this population often have accessibility problems to formal care services due to their financial and social disadvantages. In a high-income, developed Chinese society, this pragmatic randomized controlled trial seeks to investigate the effect of a 6-months lay health worker intervention in diabetes management among people living in sub-divided flats units in Hong Kong. Methods and Analysis: In this trial, 222 Chinese primary caregivers living in inadequate houses and with diabetes risk will be recruited via non-profit organizations serving in districts with low average household incomes and prevalent subdivided flats in HK. Adopting a 3 months wait-list control, participants will be randomized to receive a 6-months lay health worker intervention of 5 components, including 1) lay health worker training and support; 2) health professional training; 3) formulation of a targeted care plan for the health and nutritional needs of the families; 4) case management approach; and 5) financial subsidy for lay health workers to sustain the practice. The control group will receive usual care and health information on diabetes risk management. Glycated hemoglobin and fasting blood glucose will be taken at the entry and exit assessment of this trial as primary outcomes. Discussion: Our randomized controlled trial is one of the first to investigate the effect of lay health worker intervention on pre-diabetes management in a low-income Chinese population residing in inadequate houses. This study could provide insights to consider alternative service provision models to people living with diabetes risk in the community, by providing a care option to be supported by community health workers and enhanced community participation of care providers. This study attempts to evaluate the impact of a lay health worker intervention using a mixed-method study design. Despite its contribution, this study might be subjected to sampling bias since all the participants will be recruited from non-profit organizations serving deprived populations.